2012
DOI: 10.1590/s0102-77862012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six empirical evapotranspiration equations - case study: Campos dos Goytacazes/RJ

Abstract: The evapotranspiration is a component of the water balance constituting a major challenge in its quantification. The complex physical processes involved in its effective determination on a large scale have spurred scientists to often make use of empirical equations, which have inherent limitations with regard to their applicability as descriptors of the evapotranspiration behavior in different regions across the world. This study was performed for the Campos dos Goytacazes region, in Rio de Janeiro state. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
3
9
0
5
Order By: Relevance
“…The performance of Jensen-Haise equation at Tessalit is in agreement with [55] who reported large discrepancies when using this equation under extremely arid condition like the Saharan arid climate at Tessalit. Similar to the results of this study, the Jensen-Haise equation presented also the highest RMSE of 1.63 mm/day with a relative error over 40% in the State of Rio de Janeiro, Southeast of Brazil [56]. However, [57] reported that the Jensen-Haise equation was the best among 23 ETo methods evaluated under the extremely arid climate conditions in the central Saudi Arabia.…”
Section: Evaluation Of the Selected Eto Equationssupporting
confidence: 84%
“…The performance of Jensen-Haise equation at Tessalit is in agreement with [55] who reported large discrepancies when using this equation under extremely arid condition like the Saharan arid climate at Tessalit. Similar to the results of this study, the Jensen-Haise equation presented also the highest RMSE of 1.63 mm/day with a relative error over 40% in the State of Rio de Janeiro, Southeast of Brazil [56]. However, [57] reported that the Jensen-Haise equation was the best among 23 ETo methods evaluated under the extremely arid climate conditions in the central Saudi Arabia.…”
Section: Evaluation Of the Selected Eto Equationssupporting
confidence: 84%
“…Furthermore, Kalma et al (2008), conducted a review of 30 remote sensing ET modelling results relative to ground based measurements and contended that the ground based measurement methods were not incontrovertibly more reliable than the remote sensing ET modelling methods. Moreover, most of the ground based measurement methods are usually cost intensive thereby constraining measurements over large areas and thus making spatial extrapolation difficult (Moran and Jackson, 1991;Verstraeten et al, 2008;Melesse et al, 2009;Fernandes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is indicator of the deviation in estimation [1] of ET. The corresponding relative RMSE (rRMSE) is the ratio of RMSE divided by the mean value of ET-PM, which when multiplied by 100% gives the relative error [11]. These values are given in parenthesis next to RMSE values in Tables 4 and 6.…”
Section: Mathematical Methods Of Evaluating the Statistical Parametermentioning
confidence: 99%
“…The use of FAO56-PM equation is the recommended method to estimate potential evapotranspiration of a given location. The equation is physically based [1] and therefore provides consistent ET in many regions and climates without any need to estimate additional parameters [6,11]. But it requires many meteorological variables such as input of temperature, wind speed, relative humidity and radiation that limit its widespread use [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation